Metabolic susceptibility to agricultural pesticides and non-Hodgkin’s lymphoma - Schroeder, J. C. (Scandinavian Journal of Work, Environment & Health, 2005)
Epidemiologic studies have failed to establish clearly whether agricultural pesticides contribute to the genesis of non-Hodgkin’s lymphoma (NHL). Discordant results may be related to variation in susceptibility factors, including metabolism gene polymorphisms that might influence lymphocyte exposures to active pesticide metabolites. Associations between NHL and polymorphisms that may be relevant to pesticide metabolism have been assessed, including CYP1A1 and glutathione S-transferase variants, but the results are not highly informative because estimates were based on small numbers and convenience samples of cases and controls. Butyrylcholinesterase and paraoxonase (PON1) enzyme variants associated with altered activity and acute organophosphate toxicity are strong candidate susceptibility factors for pesticides and NHL, but others may be identified as knowledge of pesticide metabolism and relevant polymorphisms improves. Studies of metabolic susceptibility must be large and include information on specific exposures and subtypes of NHL for results to further the understanding of the relation between agricultural pesticides and NHL.
Keywords: agricultural pesticide; butyrylcholinesterase; cytochrome P-450; gene-environment interaction; glucuronosyltransferase; glutathione S-transferase; metabolic susceptibility; non-Hodgkin’s lymphoma; paraoxonase; polymorphism; review; sulfotransferase